PENERAPAN NON FINANCIAL PERFORMACE MEASURES DALAM MENGUKUR KINERJA BAGIAN PRODUKSI UNTUK MENINGKATKAN KEPUASAN CUSTOMER - Visensia Lukika; Ria Sandra Alimbudiono (Perpustakaan Universitas Surabaya, 2018)
This study aims to help companies measure performance related to production sector through nonfinancial performance measures from various aspects of production by making corrective action to problems. Financial performance measurement is more commonly used but cann’t represent overall performance of company as it only measures figures in financial statements without considering nonfinancial factors of company. Non-financial measurements are oriented towards continuous improvement to improve efficiency,productivity and overcome competition obstacles. This research uses qualitative approach which is exploratory research because this study is expected to assist management in terms of performance measurement by applying Non Financial Performance Measures which will help company to achieve performance improvement. This research is done in production section to help improve product to increase customer satisfaction. Measurements made are supplier performance, defect rate, productivity and rate of return and warranty. Data collection is done by interviews, observation and document analysis.This study find that companies still need to make better performance measurements on tproduction. Companies need to record and use measurements so improvements can be achieved. There are various weaknesses in the application, so this study only provides recommendations for improvement of problem by providing other performance measures to improve performance and decision making.